Patient-reported outcome was close to the Danish background population 6 months after non-surgical treatment of Neer 2-part surgical neck fractures: a prospective cohort study in patients aged 60 or above - Stig Brorson; Signe A Borg; Line L Houkjær; Kenneth B Holtz; Zaid Issa (Acta Orthopaedica)
Background and purpose: Neer 2-part surgical neck fractures are the most common displaced proximal humerus fractures. We aimed to evaluate patient-reported outcome in a consecutive series of older people receiving nonoperative treatment. Methods: This is a single-center prospective cohort study. We included patients aged 60 or above referred to a Danish university hospital. The preregistered protocol followed the recommendations from randomized trials. Patients were followed at the outpatient clinic at 2, 6, and 24 weeks. After 24 weeks, they were evaluated with Oxford Shoulder Score (OSS, 0–48, 48 best) and EuroQoL 5 dimensions, 3 levels (EQ-5D-3L, –0.624 to 1, 1 best). Clinical failure was defined as conversion to surgery or OSS ≤ 24. Population norms were reported to interpret the cohort data, but no formal statistical comparisons between historical cohorts were planned. We used descriptive statistics to report rates and proportions. Results: For 36 months, 268 patients (mean age 76, 79% female) with Neer 2-part surgical neck fractures received non-surgical treatment. After excluding patients with concomitant fractures, dementia, or death, complete follow-up was available for 167 patients. 8 patients (3.0%) had surgery. The mean OSS was 37.2 (SD 8.1), which equals 78% of maximum shoulder function. The norm for the population of the same age and gender was 82%. The mean EQ-5D-3L score was 0.79 (SD 0.16), while the norm for the same-age population was 0.82. 16 (10%) had an OSS score of 24 or below. Conclusion: Non-surgical treatment in older people with Neer 2-part surgical neck fractures resulted after 6 months in patient-reported shoulder function and quality of life close to that of the Danish background population.